Sistema de riego para bosques y sistema de control contra incendios ejemplarizado en un sector del Parque Nacional Cotopaxi - Almachi Villareal, Carina Alejandra (2014)
With the increase of forest fire by hot seasons in recent years, the Cotopaxi National Park has affected thousands of acres of forest; therefore the location of an Irrigation System, which is divided into 3 zones, tanks supply was sized with a running 3 hours, the Environmental Impact Assessment found that negative impacts such as erosion and disruption was performed is presented to the soil quality, a result of excavation and construction activities; however, the positive impact is the generation of jobs, the results with the Management Plan for the prevention and mitigation plans, contingency, community relations, monitoring and prevention of forest fires was set.